New Genes Involved in Mild Stress Response Identified by Transposon Mutagenesis in Lactobacillus paracasei - Palud, Aurore; Scornec, Hélène; Cavin, Jean-François; Licandro, Hélène (Frontiers in Microbiology, 2018)
Lactic acid bacteria (LAB) are associated with various plant, animal and human niches and are also present in many fermented foods and beverages. Thus, they are subjected to several stress conditions and have developed advanced response mechanisms to resist, adapt, and grow. This work aimed to identify the genes involved in some stress adaptation mechanisms in LAB. For this purpose, global reverse genetics was applied by screening a library of 1287 Lactobacillus paracasei transposon mutants for mild monofactorial stresses. This library was submitted independently to heat (52 °C – 30 min), ethanol (170 g.L-1, 30 min), salt (NaCl 0.8 M, 24h), acid (pH 4.5, 24 h) and oxidative (2 mM H2O2, 24 h) perturbations which trigger mild monofactorial stresses compatible with bacterial adaptation. Stress sensitivity of mutants was determined either by evaluating viability using propidium iodide (PI) staining, or by following growth inhibition through turbidity measurement. Transposon insertions in 63 genes or putative promoters led to an increased sensitivity to the heat stress whereas they lead to an increased sensitivity to ethanol for 27 genes or putative promoters. Among them, 14 genes or putative promoters were common for both stresses. For salt, acid and oxidative stresses, respectively 8, 6 and 9 genes or putative promoters were identified as essential for adaptation to these stresses, with only 3 genes common to at least two stresses. Then, RT-qPCR was performed on selected stress response genes identified by mutant screenings in order to evaluate if their expression was modified in response to stresses in the parental strain. Eleven genes were upregulated during stress adaptation for at least two stresses. Seven genes, encoding membrane functions, were upregulated in response to a specific stress and thus could represent potential transcriptomic biomarkers. The results highlights that most of the genes identified by global reverse genetics are specifically required in response to one stress and that they are not differentially transcribed during stress in the parental strain. Most of these genes have not been characterized as stress response genes and provide new insights into the adaptation of lactic acid bacteria to their environment.